Association between breastfeeding and new mothers' sleep: a unique Australian time use study - Julie P. Smith; Robert I. Forrester (BMC, 2021)
Abstract Background Infant sleep is of great interest to new parents. There is ongoing debate about whether infants fed with breastmilk substitutes sleep longer than those exclusively or partially breastfed, but what does this mean for the mother? What expectations are realistic for mothers desiring to exclusively breastfeed as recommended by health authorities? There are both biological and social influences on infant and maternal sleep. More accurate information on average maternal sleep hours for diverse feeding practices may help guide realistic expectations and better outcomes for mothers, infants and families. Methods Using a unique time use dataset purposefully designed to study the time use of new mothers, this study investigated whether the weekly duration of maternal sleep, sleep disturbance, unpaid housework, and free time activities differed by detailed feeding method. The study collected 24/7 time use data from 156 mothers of infants aged 3, 6 and/or 9 months between April 2005 and April 2006, recruited via mother's groups, infant health clinics, and childcare services throughout Australia. Sociodemographic and feeding status data were collected by questionnaire. Statistical analysis used linear mixed modelling and residual maximum likelihood analysis to compare effects of different infant feeding practices on maternal time use. Results There were no significant differences in time spent asleep between lactating and non lactating mothers, though lactating mothers had more time awake at night. Lactating mothers spent more time (8.5 h weekly) in childcaring activity (p = 0.007), and in employment (2.7 vs. 1.2 h, p < 0.01), but there were no significant differences in free time. Those not breastfeeding spent more time in unpaid domestic work. Exclusive breastfeeding was associated with reduced maternal sleep hours (average 7.08 h daily). Again, free time did not differ significantly between feeding groups. Exclusively breastfeeding mothers experienced reduced sleep hours, but maintained comparable leisure time to other mothers by allocating their time differently. Domestic work hours differed, interacting in complex ways with infant age and feeding practice. Conclusions Optimal breastfeeding may require realistic maternal sleep expectations and equitable sharing of paid and unpaid work burdens with other household members in the months after the birth of an infant.